The lithium effect on learning and memory deficits and hippocampal level of BDNF in prenatal seizure kindled rats - Mohammad Amin Edalatmanesh; Khadijeh Amooei (Fasa University of Medical Sciences, 2018)
Background & Objective: Prenatal seizures cause neuronal damage in the limbic area of fetal brain leading to learning deficits and cognitive impairment in newborns. This study examined the effect of prenatal tonic-clonic seizure and lithium chloride (LiCl) therapy on the learning and memory of rat's pups. Materials & Methods: Pregnant Wistar rats were kindled by (i.p) injections of 40 mg/kg/BW of Penthylentetrazole (PTZ) on embryonic day (ED) 13 for 7 consecutive days. LiCl treated rats in PTZ+Li0.04, and PTZ+Li0.08 groups received 0.04% and 0.08% of LiCl in tap water from ED10 to postnatal day (PND) 24, respectively. The spatial performance learning was evaluated at PND 30 using Morris water maze (MWM). After behavioral study, the hippocampal level of BDNF was measured using ELISA. Results: In comparison to controls, PTZ group showed a significant increase in latency time and distance to hidden platform in MWM test and decrease level of hippocampal BDNF. LiCl-treated rats showed a significant lower latency time and distance to hidden platform in MWM and higher level of BDNF than PTZ group. Conclusion: The LiCl with elevated of BDNF in hippocampus can ameliorate spatial memory in prenatal seizure model.